A review of the degradation mechanisms of NCM cathodes and corresponding mitigation strategies - Britala, Liga; Marinaro, Mario; Kucinskis, Gints (Journal of energy storage, 2023)
Li-ion batteries (LIBs) are the most widely used form of energy storage in mobile electronic devices and electric vehicles. Li-ion battery cathodes with the composition LiNixMnyCozO2 (NCMs) currently display some of the most promising electrochemical characteristics for high performance LIBs. NCM compositions with high nickel content (x > 0.8) exhibit the largest specific capacity while undergoing fast degradation and presenting safety issues. As the main degradation mechanisms of NCM materials and the mitigation of their degradation, are still subjects of many ongoing studies, this work summarizes the current knowledge on the subject. Here, the existing literature is reviewed to present the structural and electrochemical degradation of NCM with varying Ni stoichiometries (NCM111, NCM622, NCM811, and beyond). Routes for hindering the degradation of NCM are discussed as a function of Ni content in NCM and include doping, application of protective coatings, and engineering of the microstructure. A comprehensive understanding of the main degradation pathways of NCM is key to applying the most appropriate mitigation strategies and keep advancing towards higher energy NCM materials with longer cycle-life. •This review summarizes NCM degradation mechanisms and their mitigation.•Degradation mechanisms and corresponding mitigation vary with Ni content.•Main mitigation techniques are microstructural modification, coating and doping.•Coating is more efficient for NCMs with lower Ni content.•Doping is crucial with higher Ni content in NCM to mitigate volume changes.